Analisis Pengaruh Profitabilitas, Likuiditas, Dan Kepemilikan Asing Terhadap Struktur Modal Dengan Kepemilikan Manajerial Sebagai Variabel Moderasi - Harta Daya, Viviana Oktaviani; Hermuningsih, Sri; Rinofah, Risal (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Is study aims to determine the effect of the effect of Profitability, Liquidity, Foreign Ownership, on Capital Structure with Managerial Ownership as a Moderating Variable in Mining companies on BEI 2018-2022. This research is quantitative using secondary data from the financial statements of mining companies on the BEIr a 5-year period. The data is processed using IBM SPSS Statistics 24.0. The findings of this study indicate that profitability affects the capital structure, liquidity does not affect the capital structure, foreign ownership negatively affects the capital structure and managerial ownership as a moderating variable is not able to moderate the liquidity variable, and foreign ownership. While managerial ownership is able to moderate the profitability variable.